Structural Design and Mechanical Analysis of Permanent Magnet Wheeled Climbing Robots on an Outer Wall of Pipelines - Li Haonan; Hou Yu; Jiang Yiwei; Sun Wei (Jixie chuandong)
Large pipelines with long term transport of oil and gas resources need to be tested in petrochemical industry nowadays. In this case, a robot which adopts a six-wheel rocker-bogie mobile mechanism with the permanent magnet wheel is proposed to realize the function of the stability to walk on the outer wall and good ability to climb over the obstacle, in order to replace manual inspection of pipelines in a safer and more efficient way when it is equipped with the testing equipment. To determine the driving force required, the minimum magnetic force meeting the force balance condition of stable adsorption of the robot needs to be calculated first; the size of the permanent magnet wheel is designed and determined based on the magnetic force analysis model of the permanent magnet wheel established by Maxwell. Kinematics simulation of the robot based on Adams software is carried out and the ability to climb over the obstacle is verified.